Acute post-traumatic muscle atrophy on CT scan predicts prolonged mechanical ventilation and a worse outcome in severe trauma patients. Issue 7 (July 2022) - Tazerout, Sonia; Martinez, Orianne; Monsonis, Benjamin; Millet, Ingrid; Taourel, Patrice; Capdevila, Xavier; Charbit, Jonathan
ABSTRACT: Background: The aim of present study was to assess the association between acute post-traumatic atrophy (APTMA) determined on psoas computed tomography [CT] scan and the duration of mechanical ventilation and outcomes in severe trauma patients. Methods: A retrospective analysis of severe trauma patients (Injury Severity Score [ISS], >15) hospitalized in the intensive care unit (ICU) for more than 7 days between January 2010 and December 2015 was performed. The psoas muscle index (PMI) was measured on admission and at delayed CT scan. ΔPMI was calculated as the percentage PMI loss between these two scans. Three groups were defined and compared a posteriori using the quartiles of the ΔPMI values: low (lower quartile), moderate, and severe (higher quartile) APTMA groups. Linear regression analysis was performed to predict the duration of mechanical ventilation, of catecholamines, length of stay (LOS) in the ICU and hospital, and complications were assessed. Results: A total of 114 trauma patients were included (median age, 40 years; [IQR, 25–54 years]; ISS, 33 [IQR, 25–41]). Based on the ΔPMI determination, 29 patients were allocated in the low APTMA group (range ∆PMI, 0%–6%), 56 in the moderate APTMA group (range ∆PMI, 6%–18%), and 29 in the APTMA group (range ∆PMI, ≥19%). Severity of APTMA was significantly associated with the duration of mechanical ventilation and catecholamines, ICU and hospital LOS ( P <0.001). Delayed pneumonia ( P =0.006) and other delayed infections ( P =0.014), as well as thromboembolic events ( P =0.04) were statistically associated with the severity of APTMA, whereas mortality did not differ between the three groups ( P =0.20). Using linear regression analysis, each ∆PMI increase of 1% was significantly associated with 0.90 supplementary days of mechanical ventilation ( P <0.001), 0.29 supplementary days of catecholamines ( P <0.001) and 0.82 supplementary days of hospitalization ( P <0.001). All these statistical associations were confirmed in multivariate analysis ( P <0.001). Conclusion: Acute muscle atrophy diagnosed on CT scan by psoas area measurement (ΔPMI) was strongly associated with poor outcomes in severe trauma patients.